Pros and Cons of the Latest Pencak Silat Match Rules in Indonesia - Faris Aman Sad; Nur Subekti; Rony Syaifullah (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The establishment of the latest pencak silat rules passed by PERSILAT in 2021 has led to various perceptions that lead to differences of opinion from pencak silat practitioners. The purpose of this study is to observe the perceptions of pencak silat practitioners in Indonesia about the plan to enforce the pencak silat competition regulations. This research method uses quantitative and qualitative approaches. The target subjects in the study amounted to 513 respondents which included: administrators, coaches, and pencak silat athletes throughout Indonesia, with data collection techniques using purposive sampling. The data analysis technique uses data reduction, data presentation and conclusion drawing followed by descriptive frequency analysis. The survey on the application of pencak silat match rules in 2021 consists of: (1) knowledge of match rules, (2) training preparation; (2) athlete safety level; and (3) suggestions or input for improvement. The results showed that of the 513 respondents, more than half (89.1%) of the respondents knew about the regulations that would be applied, the rest did not know about the implementation of the latest pencak silat match regulations. Based on the level of safety of athletes from 391 respondents more than half chose a higher risk of injury or 65%. However, further research is needed related to socialization and assistance, both from administrators, coaches, athletes, and all Indonesian pencak silat practitioners.